Barriers and Challenges of Death Penalty Implementation against Corruption Crimes Perpetrators in Indonesia - Zulfan; Husni; Muhammad Hatta; Ramalinggam Rajamanickam (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
Since the enactment of the anti-corruption law, no perpetrators of corruption in Indonesia have been sentenced to death. The obstacle to implementing the death penalty for corruptors lies in the provisions set forth in Article 2 paragraph (2) of Law No. 31 of 1999 and its Jo. Law No. 20 of 2001 regarding the corruption eradication, which specifies that the death penalty can only be imposed under certain circumstances. The interpretation of